Rushmore - Mothersbaugh, Mark 1950- (<<The>> Criterion collection, 2018)
"The dazzling sophomore film from Wes Anderson is equal parts coming-of-age story, French New Wave homage, and screwball comedy. Tenth grader Max Fischer (Jason Schwartzman) is Rushmore Academy’s most extracurricular student—and its least scholarly. He faces expulsion and enters into unlikely friendships with both a lovely first-grade teacher (Olivia Williams) and a melancholy self-made millionaire (Bill Murray, in an award-winning performance). Set to a soundtrack of classic British Invasion tunes, Rushmore defies categorization, capturing the pain and exuberance of adolescence with wit, emotional depth, and cinematic panache." [criterion.com]
Original: USA 1998
director-approved Blu-Ray special edition features: digital transfer of the director’s cut, supervised by director Wes Anderson, with DTS-HD Master Audio soundtrack on ; audio commentary featuring Anderson, cowriter Owen Wilson, and actor Jason Schwartzman ; "the Making of 'Rushmore'", an exclusive behind-the-scenes documentary by Eric Chase Anderson ; Max Fischer Players present, theatrical "adaptations" of Armageddon, Out of Sight, and The Truman Show, staged for the 1999 MTV movie awards ; episode of The Charlie Rose Show featuring Wes Anderson and actor Bill Murray ; audition footage ; Anderson’s hand-drawn storyboards, plus a film-to-storyboard comparison ; original theatrical trailer ; collectible poster ; plus: a new essay by film critic Dave Kehr
Bildformat 2.35:1
Keywords: Film; Blu-Ray-Disc